Tayangan Televisi: Akhlak dan Buruh Industri: Sebuah Tantangan dan Peluang Dakwah Islamiyah - Ali, Syauki (Tasamuh: Jurnal Studi Islam, 2020)
The mass media that develops in the community have a variety of forms. There are mass media in the form of audio mass media (in the form of sounds), visual mass media (in the form of images, both non-moving images and moving images), and audio-visual mass media (in the form of sounds and images). Nowadays, the mass media which are the most widely owned and used as media of information, entertainment, education, and social controlled by the public are mostly mass media in the form of television. This media (television) has its own advantages where people can enjoy objects of information and communication in the form of audio-visual at the same time. The existence of mass media including television occupies a place that is urgent, because the mass media in addition to being a medium of communication (channel of communication) that functions as a messenger and acts as a source of messages (massage resource). Television excels in building attraction, perception, change and imagination in constructing reality. Through television, people can choose various shows that are needed by them. These shows are news, entertainment, or educational information shows. While other television station programs offer a very physical, materialistic luxury, Trans 7 offers a different alternative. The talk show so-called Empat Mata, which has now changed its name to not four eyes, was delivered by the presenter, as well as comedian Tukul Arwana who presents contextually related to people’s interest that is effortlessly undertood, immidiately accepted, and non-complicated interpretation to figure out its purpose. This paper reviews the role of television shows on morals and the role of industrial workers in the world of intertiment.